Adaptive management of declining fisheries: When is it worth trying to rebuild stocks through fishery regulation?. (November 2017) - Ben-Hasan, A.; Al-Husaini, M.; Walters, C.
Abstract: Declining catches are typically taken to be a warning sign of overfishing. But in fact, many such declines have been driven by recruitment changes unrelated to stock size, as evidenced by the failure of stocks to recover after reduction in fishing or recovery despite the failure to reduce fishing. Given a declining pattern, supposedly precautionary decisions to reduce fishing should be treated as experimental management options with a high probability of not resulting in the desired recovery to more productive stock sizes. Simple decision tables can be used to compare such experimental options to "wait and see" options that do not involve fishing reductions. A case example with a grouper fishery in Kuwait demonstrates that experimental effort reduction may not be the best policy from a decision analysis perspective, at least when there are substantial reasons to expect recruitment changes unrelated to stock size. In this case, virtual population analysis and stock reduction analysis models indicate either unusually weak recruitment compensation (steepness h < 0.4) or progressive decline in recruitment carrying capacity, possibly caused by decreases in estuarine rearing habitat associated with declining flows of the Tigris and Euphrates Rivers.